2018
DOI: 10.20341/gb.2018.010
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial origin of the red pigmentation of Phanerozoic carbonate rocks: an integrated study of geology-biology-chemistry (Ernest Van den Broeck medallist lecture 2017)

Abstract: Explaining the color of rocks is still a complex problem. This question was raised long ago in the community of geologists, particularly for the pigmentation of the 'red marbles' of the Frasnian of Belgium at the beginning of the last century, with many unsatisfactory hypotheses. Our recent analysis of different red carbonate rocks in Europe and North Africa (Morocco) may provide an alternative explanation for the color of these rocks. For this it was necessary to bring together diverse and complementary skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The role of bacterial activity in Fe(II) to Fe(III) transformation, as suggested by Mamet & Préat (2006) and Préat et al . (2018), for marine red beds should not be undervalued. Microbial decomposition of organic matter in CRBs is supported by haloes of reduced iron found around burrows and root traces in palaeosols (Retallack, 1990; Wright et al ., 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The role of bacterial activity in Fe(II) to Fe(III) transformation, as suggested by Mamet & Préat (2006) and Préat et al . (2018), for marine red beds should not be undervalued. Microbial decomposition of organic matter in CRBs is supported by haloes of reduced iron found around burrows and root traces in palaeosols (Retallack, 1990; Wright et al ., 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of iron coccoid-like clusters and geometries within the red mudstone facies of Menorcan MRBs could point to the activity of Fe-fixing bacteria and their contribution towards the coloration of MRBs. However, it is known that iron-bacteria are eliminated under highly oxidizing conditions (Fenchel and Finlay, 1995;Préat et al, 2018), which may rule-out iron-bacteria as an important contributor for the red staining. Préat et al (2006) suggested a mechanism for the Ammonitico Rosso facies, where the presence of dysoxic to anoxic bottom-water conditions inhibited the spread of burrowers and subsequently prevented the colonization with iron-oxidizing biofilms which ultimately form hematite.…”
Section: Comments On the Origin Of The Red Coloration In Menorcan Mar...mentioning
confidence: 99%
“…Bacterial activity was certainly a factor in the development of the pink colour of the Danian couplets (Fig. 9e-h); however, in the absence of more precise studies, it cannot be considered the primary cause of the red colouring in the case of the Basque-Cantabrian Basin, even though other authors consider iron-oxidizing bacteria to be the main cause of such tones in their studies on other areas (Mamet et al 1997;Della Porta et al 2003;Mamet & Préat, 2005Préat et al 2006Préat et al , 2018Van der Kooij et al 2007;Song et al 2017). Nanobacteria with coalescent structure forms (< 0.1 μm) thrive in the superficial part of the coccolith plates and ferromagnesian clays, with a strong similarity to those reported by Mamet & Préat (2006, fig.…”
mentioning
confidence: 91%